2023
DOI: 10.3390/ma16155271
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Multiple Used Implant Drills on Their Cutting Performance and Fracture Resistance

Abstract: This study aimed to analyze the influence of multiple uses of zirconia implant drills on their cutting performance and bending strength. The hypothesis was that drill usage and sterilization cycles would not affect drilling time or flexural strength. Sixty zirconia twist drills from Z-Systems were used to drill in the angulus mandibulae region of fresh porcine jaws. The drills were divided into four groups based on the cycle count, and the drilling time was measured. Bending strength tests were conducted using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…While numerous technical studies have explored methods to mitigate the heat effects on bone, such as utilising coolant irrigation, optimising drill bit geometry [9], enhancing wear resistance [47], implementing step-power drilling [48], etc., there is no conclusive evidence to indicate that irrigation cooling is universally adopted as a standard practice, despite strong recommendations from major implant manufacturers. However, clinically, irrigation cooling is standard practice and is strongly advocated for by leading implant manufacturers [49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While numerous technical studies have explored methods to mitigate the heat effects on bone, such as utilising coolant irrigation, optimising drill bit geometry [9], enhancing wear resistance [47], implementing step-power drilling [48], etc., there is no conclusive evidence to indicate that irrigation cooling is universally adopted as a standard practice, despite strong recommendations from major implant manufacturers. However, clinically, irrigation cooling is standard practice and is strongly advocated for by leading implant manufacturers [49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the contact interaction properties must be defined for the contact pair. An assumption is made that Coulomb's friction law governs the friction behaviour between the drill bit and bone; the coefficient of friction is assumed to be 0.3 [9].…”
Section: Construction Of Fe Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the contact interaction properties must be defined for the contact pair. An assumption is made that Coulomb’s friction law governs the friction behaviour between the drill bit and bone: the coefficient of friction is assumed to be 0.3 [ 9 ]. The thermal conductivity for cortical bone and drill bit are 0.452 and 16.2 (W/m·k), respectively [ 39 , 40 ].…”
Section: Finite Element (Fe) Modellingmentioning
confidence: 99%
“…It has been shown that temperatures over 50 °C are associated with irreversible changes in bone structure and physical properties [ 1 , 2 ]. The necrotic bone is resorbed through osteoclast activity, posing potential risks to the stability of bone screws and pins and ultimately leads to the failure of the fracture repair or implant fixation [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Consequently, some studies have focused on the rise in temperature during bone drilling and the associated necrosis phenomenon.…”
Section: Introductionmentioning
confidence: 99%